The design and modification of a parabolic trough system for the hydrothermal liquefaction of waste - Almond, Heather; Tonnellier, Xavier; Sansom, Christopher L.; Pearce, Matt; Sengar, Namrata (American Institute of Physics (AIP), 2019)
We describe the design of a small-scale parabolic trough with a high-pressure absorber bundle to convert microalgae into bio-oil. The “proof-of-concept” system uses an existing Global CSP solar captor, with its reflectance enhanced by the addition of Skyfuel® ReflecTech Plus polymer film and has its original receiver tube replaced by a novel high-pressure multi-tube absorber and reactor. Initial results obtained at Kota University in Rajasthan, India demonstrated that temperatures up to 320°C are possible, and a bio-oil, similar to palm oil, was extracted from the reactor.